Horizontal and vertical movements of Caribbean reef sharks (Carcharhinus perezi): conservation implications of limited migration in a marine sanctuary - Shipley, Oliver N. (R Soc Open Sci, 2017)
Despite the ecological and economic importance of the Caribbean reef shark (Carcharhinus perezi), little data exist regarding the movements and habitat use of this predator across its range. We deployed 11 pop-up satellite archival tags on Caribbean reef sharks captured in the northeast Exuma Sound, The Bahamas, to assess their horizontal and vertical movements throughout the water column. Sharks showed high site fidelity to The Bahamas suggesting Bahamian subpopulations remain protected within the Bahamian Shark Sanctuary. Depth data indicate that Caribbean reef sharks spent a significant proportion (72–91%) of their time above 50 m in narrow vertical depth bands, which varied considerably on an individual basis. This may be indicative of high site fidelity to specific bathymetric features. Animals exhibited three broadly categorized sporadic off-bank excursions (more than 50 m excursions) down to a depth of 436.1 m, which were more frequent during the night. These deeper excursions during night may be indicative of foraging in relation to prey on mesophotic reefs, as well as diel-vertically migrating prey from the deeper meso- and bathypelagic zones. These vertical movements suggest that Caribbean reef sharks can be significant vectors of ecosystem connectivity further warranting holistic multi-system management and conservation approaches.